Testosterone in males with COVID‐19: a 12‐month cohort study. (27th October 2022) - Salonia, Andrea; Pontillo, Marina; Capogrosso, Paolo; Pozzi, Edoardo; Ferrara, Anna Maria; Cotelessa, Alice; Belladelli, Federico; Corsini, Christian; Gregori, Silvia; Rowe, Isaline; Carenzi, Cristina; Ramirez, Giuseppe A.; et al.
Abstract: Background: Male patients with COVID‐19 have been found with reduced serum total testosterone (tT) levels and with more severe clinical outcomes. Objectives: To assess total testosterone (tT) levels and the probability of recovering eugonadal tT levels during a minimum 12‐month timespan in a cohort of men who have been followed over time after the recovery from laboratory‐confirmed COVID‐19. Materials and methods: Demographic, clinical and hormonal values were collected for the overall cohort. Hypogonadism was defined as tT ≤9.2 nmol/l. The Charlson Comorbidity Index was used to score health‐significant comorbidities. Descriptive statistics was used to compare hormonal levels at baseline versus 7‐month (FU1) versus 12‐month (FU2) follow‐up, respectively. Multivariate cox proportional hazards regression model was used to identify the potential predictors of eugonadism recovery over time among patients with hypogonadism at the time of infection. Results: Of the original cohort of 286 patients, follow‐up data were available for 121 (42.3%) at FU1 and 63 (22%) patients at FU2, respectively. Higher median interquartile range (IQR) tT levels were detected at FU2 (13.8 (12.3–15.3) nmol/L) versus FU1 (10.2 [9.3–10.9] nmol/L) and versus baseline (3.6 [3.02–4.02] nmol/L) (all p  < 0.0001), whilst both LH and E2 levels significantly decreased over the same time frame (all p  ≤ 0.01). Circulating IL‐6 levels further decreased at FU2 compared to FU1 levels (19.3 vs. 72.8 pg/ml) ( p  = 0.02). At multivariable cox regression analyses, baseline tT level (HR 1.19; p  = 0.03 [1.02–1.4]) was independently associated with the probability of tT level normalization over time, after adjusting for potential confounders. Conclusions: Circulating tT levels keep increasing over time in men after COVID‐19. Still, almost 30% of men who recovered from COVID‐19 had low circulating T levels suggestive for a condition of hypogonadism at a minimum 12‐month follow‐up.